2017
DOI: 10.1007/s40477-017-0246-5
|View full text |Cite
|
Sign up to set email alerts
|

Focused cardiac ultrasound (FOCUS) by emergency medicine residents in patients with suspected cardiovascular diseases

Abstract: FOCUS performed by emergency medicine residents is comparable to echocardiography performed by cardiologists. Therefore, it could be a reliable tool and screening test for initial testing of patients suspected of cardiac abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 17 publications
0
61
1
2
Order By: Relevance
“… 8 Previous studies have demonstrated that POCUS performed by emergency medicine residents is comparable to echocardiography performed by cardiologists. 9 Even in the hands of a non-POCUS focused EP, it was evident upon first glance that the heart in this case was abnormal. We feel that any EP with the most basic emergency echocardiography education would have identified the “abnormal” large mass/thrombus visualized in this case.…”
Section: Discussionmentioning
confidence: 74%
“… 8 Previous studies have demonstrated that POCUS performed by emergency medicine residents is comparable to echocardiography performed by cardiologists. 9 Even in the hands of a non-POCUS focused EP, it was evident upon first glance that the heart in this case was abnormal. We feel that any EP with the most basic emergency echocardiography education would have identified the “abnormal” large mass/thrombus visualized in this case.…”
Section: Discussionmentioning
confidence: 74%
“…or ventriculogram88 (75–96)92 (75–99)11.5 (3.1–43.7)0.13 (0.05–0.29)Speckle trackingReardon et al [53]EP2018USANR751652Cardiologist echo. or final diagnosis ACS29 (17–46)88 (72–96)2.4 a 0.81 a Pericardial effusionMandavia et al [54]EP2001USA5 h.51520NRCardiologist echo.96.0 (90.4–98.9)98.0 (95.8 to 99.1)48.0 a 0.0408 a Farsi et al [43]EP2017Iran10 h.2051061Cardiologist echo.86 (63–96)96 (91–98)20 (10–40)0.15 (0.05–0.40)Shah et al [42]EP2016Haiti30 h.117836Cardiologist echo.88.9 (50.7–99.4)99.1 (94.2–100)98.8 a 0.112 a Bustam et al [39]EP2014Malaysia3 h.1005NRCardiologist echo.60 (15 a –95 a )100 (96 a –100 a )∞ a 0.40 a MA, meta-analysis (shown in italics with number of studies in brackets); Op., operators; Train., time spent in didactic intervention; n , size of population; Prev., prevalence; Age, medi...…”
Section: Resultsmentioning
confidence: 99%
“…However, they require more expertise and several technical pitfalls and standardization issues remain. With the widespread utilization of portable and handheld echocardiography in emergency departments and intensive care units to evaluate patient hemodynamics, LV wall motion assessment is an easier method to assess LV systolic function and is generalizable to a wider range of physicians with various level of training, expertise and echocardiographic equipment ( 24 , 25 , 26 ). We have shown herein that a simple segmental score (EF 15-40-65) applied to each of the 16 segments results in a robust estimation of LVEF by echocardiography.…”
Section: Discussionmentioning
confidence: 99%